KEUNIKAN SENI BELA DIRI JEPANG SHOURINJIKENPOU - Budi Mulyadi (Diponegoro University, 2017)
This article entitled The Uniqueness of Japan Martial Arts Shourinjikenpou The main goal of this paper writing is to know about several uniqueness of shourinjikenpou as one of martial arts from Japan. This article writing uses field reserach. Main method are observation, and interpretation. This article explains shourinjikenpou has many uniquennes such as: shourijinkenpou is combined between tradisional martial arts from China and ancient martial arts from Japan. Also shorinjikenpou contains Buddhist Teaching therefore the philosophy of shorinjikenpou is taken from buddhist teaching. Shourinjikenpou has two main stance. They are goho and juho. Thr student of shourinjikenpou has to master it before learning other stance